Regioselective Annulation of Unsymmetrical 1, 2‐Phenylenebis(diaryl/diheteroarylmethanol): A Facile Synthesis of Anthracene, Tetracene, and Naphtho[b]thiophene Analogues. Issue 35 (6th November 2015) - Sivasakthikumaran, Ramakrishnan; Rafiq, Settu Muhammad; Sankar, Elumalai; Clement, J. Arul; Mohanakrishnan, Arasambattu K.
Abstract: A systematic study on the regioselective cyclization of benzene‐ and naphthalene‐based unsymmetrical diols with HBr (33 %) in acetic acid at room temperature led to the formation of annulation products. By using this method, synthesis of a wide variety of anthracene, tetracene and naphtho[ b ]thiophene analogues was achieved in good to excellent yields. By employing HBr (33 %) in acetic acid as a catalyst for regioselective cyclization of unsymmetrical diols was very facile and devoid of commonly encountered dihydroisobenzofuran formation. Abstract : Regioselective cyclization of benzene‐ and naphthalene‐based unsymmetrical diols with HBr (33 %) in acetic acid at room temperature led to the formation of annulated arenes and heteroarenes in good to excellent yields.